Exploring Interprofessional Learning in Collaborative Care Teams: A Case Study in Primary Health Care - O’Brien, Sarah; English, Leona M. (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2022)
This study focuses on interprofessional learning and education in collaborative care teams in primary health care. Using a case study methodology, the researcher collected data through semi-structured interviews and document analysis. Through purposeful sampling, the study explores the experiences of five diverse health professionals (two nurses, two dietitians, one physician) working within collaborative care. A critical incident framework approach was used to identify interprofessional learning themes, which were classified as collaborative, continuous, and reflective. The study identified enablers to interprofessional learning as supportive time and space, trusting relationships, and shared values among team members. The interpretive framework of this study aligned experiential learning, situated cognition, and reflective practice learning theories to support the interprofessional learning process within collaborative practice teams. The study affirms the importance of informal interprofessional learning among health-care professionals.